2014
DOI: 10.1177/0950017013506772
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work experience during higher education on labour market entry: learning by doing or an entry ticket?

Abstract: Graduates from higher education often enter the labour market with a considerable amount of work experience. Using German data, we address the question of whether early work experience pays off upon labour market entry. We compare the labour market benefits of different types of work experience. This comparison allows us to more generally test hypotheses about different explanations of why education pays off. Results indicate that tertiary graduates do not profit from work experience that is unrelated to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 36 publications
5
71
1
4
Order By: Relevance
“…Following recent contributions (Robert and Saar, 2012;Weiss et al, 2014), we argue that university students may decide to work not only to pay for tuition fees or to gain financial independence, but also because work experience could represent an advantage in the job-seeking process as a graduate. Indeed, one should consider that, nowadays, competition among tertiary graduates in the transition to the labour market is likely to be stronger than in the past.…”
Section: Introductionmentioning
confidence: 98%
“…Following recent contributions (Robert and Saar, 2012;Weiss et al, 2014), we argue that university students may decide to work not only to pay for tuition fees or to gain financial independence, but also because work experience could represent an advantage in the job-seeking process as a graduate. Indeed, one should consider that, nowadays, competition among tertiary graduates in the transition to the labour market is likely to be stronger than in the past.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, Weiss et al (2014) have shown that field-specific work experience before graduating from higher education smoothens graduates' labour market integration in Germany. It would be worthwhile to investigate whether such qualitative differences within fields matter more in terms of labour market returns than in former times.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the impressive research on curricular internships and the public discourse encouraging the use of such strategies, many questions remain unanswered. First, evidence on the practical benefits of internships tends to be based on students [36] or employers (see, for example, [30,[37][38][39][40][41] expectations and perceptions. In fact, there seems to be an absence of empirical research cross-checking the perspectives of the main stakeholders involved in the development and implementation of internships (degree coordinators, supervisors), whose perceptions have been 'terra incognita' in this domain.…”
Section: Internships Within the Knowledge Economymentioning
confidence: 99%